2013
DOI: 10.1111/codi.12164
|View full text |Cite
|
Sign up to set email alerts
|

How to deal with complications after laparoscopic ventral mesh rectopexy: lessons learnt from a tertiary referral centre

Abstract: LVMR can be associated with technical complications arising from inadequate technique or from operation-specific complications that are amenable to complex revisional laparoscopic surgery with significant improvement in quality of life and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 26 publications
1
44
0
1
Order By: Relevance
“…Our series is important in quantifying a change in the incontinence score before and after operation. Restricting dissection to the anterior wall of the rectum may also reduce postoperative constipation [2,3,5,6,11]. Relief of sexual dysfunction was observed in this study in keeping with other studies [6,12].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our series is important in quantifying a change in the incontinence score before and after operation. Restricting dissection to the anterior wall of the rectum may also reduce postoperative constipation [2,3,5,6,11]. Relief of sexual dysfunction was observed in this study in keeping with other studies [6,12].…”
Section: Discussionsupporting
confidence: 90%
“…This series has also demonstrated that patients with recurrence after a perineal operation can achieve the same improvement with LVMR as those undergoing primary repair. The same improvements occur when LVMR has needed to be repeated or after the development of complications [6]. Several studies have documented improvement in incontinence after rectopexy [2,3] and some have used scoring systems to demonstrate this [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most cases of inadequate LVMR and resulting complications are amenable to remedial laparoscopic surgery as illustrated in this article [5]. Subsequent clinical reviews have shown its benefits in improved pelvic functions and patients' quality of life.…”
Section: Resultsmentioning
confidence: 96%